Taxonomy and ecology of the Cape Town Spider Crab, Macropodia falcifera (Stimpson, 1858) (Crustacea: Decapoda: Brachyura: Inachidae) - Ng, Peter K.l.; de Forges, Bertrand Richer; Jones, Georgina (Zootaxa, 2013)
The nomenclature and taxonomy of the Cape Town Spider Crab, Macropodia falcifera Stimpson, 1858, is treated. The species is rediagnosed and figured, and its ecology discussed. A key is also provided of the Indo-West Pacific species of Macropodia.